2021
DOI: 10.1037/cdp0000430
|View full text |Cite
|
Sign up to set email alerts
|

A person-centered examination of acculturation and psychological functioning among Chinese and Korean immigrant mothers in the United States.

Abstract: A person-centered examination of acculturation and psychological functioning among Chinese and Korean immigrant mothers in the United States. Cultural Diversity and Ethnic Minority Psychology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Given that acculturation extends across multiple domains (1), future research should utilize measures of heritage and US identification and values to better capture nuances in cultural orientations. That said, it is worth noting past research has not always consistently identified assimilated (21,(67)(68)(69) or separated profiles (67,70) among adult populations. As a whole, in contrast to results among adolescents and young adults (37), these findings may indicate decreased variability in cultural orientation among adults.…”
Section: Discussionmentioning
confidence: 99%
“…Given that acculturation extends across multiple domains (1), future research should utilize measures of heritage and US identification and values to better capture nuances in cultural orientations. That said, it is worth noting past research has not always consistently identified assimilated (21,(67)(68)(69) or separated profiles (67,70) among adult populations. As a whole, in contrast to results among adolescents and young adults (37), these findings may indicate decreased variability in cultural orientation among adults.…”
Section: Discussionmentioning
confidence: 99%
“…Additional sample demographics are presented in Table 1. Our sample size is similar to prior person-centered analyses (e.g., Gonzales-Backen et al, 2017; Ren et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The Cronbach's αs for this variable in the current study were .76 for behavioral acculturation toward American culture and .75 for behavioral acculturation toward Chinese culture. This measure has been validated in previous studies conducted among Chinese and Korean American samples and demonstrated adequate internal consistency (Ren et al, 2021;Vu et al, 2019).…”
Section: Behavioral Acculturationmentioning
confidence: 98%